Impact of the pandemic on hospital care for chronic pain patients in Germany - Cegla, Thomas; Hohenstein, Sven; Bollmann, Andreas; Pellissier, Vincent; Bencheva, Veronika; Schmiedl, Sven (Frontiers in Medicine, 2024)
Objectives The COVID-19 pandemic affected patients’ access to health services, including patients with severe chronic pain. Since limited data on pandemic-caused changes in pain therapy is available, we analyzed its effect on hospital-based pain treatment. Methods For this retrospective claims data analysis conducted in n = 37 hospitals, we included patients treated for a chronic pain-related diagnosis. Discharge rates stratified by region and pain unit size were analyzed for different time periods between January 2019 and June 2022. Results There was a significant decrease in day-care, inpatient interdisciplinary multimodal pain management, from a total of 5,533 hospital pre-pandemic treatments in 2019, to 3,942 in 2020 and 4,262 in 2021, with a slight increase in the first half of 2022. The extent of COVID-19-related changes differed depending on region and pain unit size. Conclusion The decreased number of hospital pain treatments during the pandemic implies a relevant analgesic undertreatment. During future pandemics, the ethical dimension of potentially non-sufficient pain treatment should be weighted against social, medical and hygienic restrictions influencing the hospitalization rate.